Neuroinflammation and Cerebrovascular Disease in Old Age: A Translational Medicine Perspective - Mario Di Napoli; Imtiaz M. Shah (Journal of Aging Research)
The incidence of cerebrovascular disease is highest in the elderly population. However, the pathophysiological mechanisms of brain response to cerebral ischemia in old age are currently poorly understood. Ischemic changes in the commonly used young animal stroke models do not reflect the molecular changes associated with the aged brain. Neuroinflammation and oxidative stress are important pathogenic processes occurring during the acute phase of cerebral ischemia. Free radical generation is also implicated in the aging process, and the combination of these effects in elderly stroke patients could explain the higher risk of morbidity and mortality. A better understanding of stroke pathophysiology in the elderly patient would assist in the development of new therapeutic strategies for this vulnerable age group. With the increasing use of reperfusion therapies, inflammatory pathways and oxidative stress remain attractive therapeutic targets for the development of adjuvant neuroprotective agents. This paper will discuss these molecular aspects of acute stroke and senescence from a bench-to-bedside research perspective.